2011
DOI: 10.1645/ge-2420.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Liver Fibrosis Associated with Experimental Fasciola hepatica Infection: Roles of Fas2 Proteinase and Hepatic Stellate Cell Activation

Abstract: We have evaluated the possible mechanisms of liver fibrosis caused by Fasciola hepatica in an animal model and in culture using immortalized human stellate cells. Liver biopsies of F. hepatica-infected rats were performed at wk 8 and 16. Serum-starved LX-2 cells, a human stellate cell line, were exposed to increasing concentrations of Fas2 antigen. The expression of key fibrosis-related genes was evaluated by qRT-PCR. There was a significant correlation between fibrogenic gene expression and both intensity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
17
0
2
Order By: Relevance
“…The infection causes cholangitis, cholangiocyte hyperplasia and biliary fibrosis, and cirrhosis may be developed in cattle with severe and persistent infection [28]; this condition may result in poor weight gain, reduced milk and meat yield, and infertility at the final stage [22,30]. Such significant economic loss due to liver fluke infection is a major public health problem in some parts of the world, especially in East Asia, East Europe, Africa and Latin America [26,27,50]. However, the pathological events in liver fluke infection-associated biliary fibrosis have not been investigated in detail at cellular levels, although the appearance of eosinophils is well known [28].…”
mentioning
confidence: 99%
“…The infection causes cholangitis, cholangiocyte hyperplasia and biliary fibrosis, and cirrhosis may be developed in cattle with severe and persistent infection [28]; this condition may result in poor weight gain, reduced milk and meat yield, and infertility at the final stage [22,30]. Such significant economic loss due to liver fluke infection is a major public health problem in some parts of the world, especially in East Asia, East Europe, Africa and Latin America [26,27,50]. However, the pathological events in liver fluke infection-associated biliary fibrosis have not been investigated in detail at cellular levels, although the appearance of eosinophils is well known [28].…”
mentioning
confidence: 99%
“…Some probable mechanisms are described for development of cirrhosis following liver fluke infection. A recent study suggested that F. hepatica infection was associated with the upregulation of mRNAs associated with hepatic fibrogenesis in vivo and in activated hepatic stellate cells (8). Furthermore, the liver fluke may secrete some metabolites that can play an immunogenic stimulatory role leading to strong humoral immune responses (9).…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency likely occurred because the studies that identified a relationship between cirrhosis and liver fluke were limited to animals, such as cattle, goats and sheep [ 65 , 66 ]. In addition, most cirrhosis is associated with Fasciola hepatica infection [ 66 , 67 ], which was not included in our analysis because of the absence of eligible studies.…”
Section: Discussionmentioning
confidence: 99%